2017
DOI: 10.1016/j.compedu.2016.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Verbal redundancy in a procedural animation: On-screen labels improve retention but not behavioral performance

Abstract: Multimedia learning research has shown that presenting the same words as spoken text and as written text to accompany graphical information hinders learning (i.e., redundancy effect). However, recent work showed that a "condensed" form of written text (i.e., on-screen labels) that overlaps with the spoken text, and thus is only partially redundant, can actually foster learning. This study extends this line of research by focusing on the usefulness of on-screen labels in an animation explaining a procedural tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Education videos are widely regarded as effective ways of increasing health-related knowledge. Given the benefits of educational animation and high levels of patient satisfaction, this method has been used in various fields of healthcare (Brame, 2016; de Koning et al, 2017). Studies have revealed that animation-based diabetes education can be effective in increasing patients’ level of knowledge (Al Owaifeer et al, 2018; Dahodwala et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Education videos are widely regarded as effective ways of increasing health-related knowledge. Given the benefits of educational animation and high levels of patient satisfaction, this method has been used in various fields of healthcare (Brame, 2016; de Koning et al, 2017). Studies have revealed that animation-based diabetes education can be effective in increasing patients’ level of knowledge (Al Owaifeer et al, 2018; Dahodwala et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It must be noted that the suggested lecturing model in these and similar studies (e.g. de Koning et al, 2017;Ari et al, 2014;Schüler et al, 2013) calls for much reduced levels of slide-text compared to the slides examined in the current study.…”
Section: Discussionmentioning
confidence: 59%
“…The key to the problem of designing and developing a learning content with effective animation is how the quality of students in terms of improving understanding for the better results. If talking about animation in learning then the subject is still too broad, because not only improve the achievement of students, but more than that animation research is about understanding learners cog-nitive thinking [13,19,27,32], attitudes [39], engagement [27,38], reasoning skills [18], behavioral performance [14,15,19,26,28,34,36,37,39], retention [20,23,24,34], prior knowledge domain [22,33], and satisfaction [20].…”
Section: Discussionmentioning
confidence: 99%
“…High prior knowledge will get better benefit if the content does not contained visual cues, otherwise visual cues facilitate learning will benefited low prior knowledge learners [33]. Speaks of the inherent behavioral performance of learners in learning, a study conducted by [34] found that verbal redundancy in which case an on-screen labeling of an instructional animation coincided with spoken text may increase retention but not its performance behaviors. About gesturing on a learning using instructional animation, there are 2 differences, mimicking the gestures has been done on 2 teaching content about mandarin and Persian character.…”
Section: Papers On Instructional Animationsmentioning
confidence: 99%